The hip hop generation : young Blacks and the crisis in African American culture - Kitwana, Bakari (Black thought and culture., 2002)
Young blacks born between 1965 and 1984 belong to the first generation to have grown up in post-segregation America. In this book Bakari Kitwana offers a sobering look at his generation's disproportionate incarceration and unemployment rates, as well as the collapse of its gender relations, and gives his own social and political analysis. He finds the pain of his generation buried in tough, slick gangsta movies, and their voice in the lyrics of rap music, "the black person's CNN." By turns scathing, funny, and analytic, The hip hop generation will stand as the testament of black youth culture at the turn of the century. With insight and understanding, Bakari Kitwana has combined the culture and politics of his generation into a pivotal work in American studies